Cost Oriented robotic arm optimised to aid independence. Issue 25 (2019) - Doyle-Kent, Mary; Fanning, Michael; O'Brien, David; Kopacek, Peter
Abstract: The aim of this research was to improve the quality of life of a wheelchair bound client living with muscular dystrophy by enabling her to perform tasks which most people take for granted, such as drinking independently. Due to the client's limited movement of her arms and neck, she was unable to lift a cup to her own mouth. To aid her in this endeavor, three different low-cost mechanical assistive concepts were created. These were presented to the client and the most suitable option was chosen to develop. Work then began on a functional prototype which was manufactured for under the 200 euro.